Improving Natural Resource Utilization: The Role Played by Renewable Energy Consumption, Environmental Sustainability, Energy Innovation, and Fintech: Evidence from an Emerging Economy - Al-Smadi, Raed Walid; Al-Smadi, Arkan Walid; Alomari, Khalid Faris; Alnsour, Ibrahim Radwan; Al-Hamad, Abd Al-Salam Ahmad; Mirzaliev, Sanjar (International Journal of Energy Economics and Policy, 2025)
Sustainable resource exploitation should be taken into consideration while considering economic growth. As economic activity increases, the significance of identifying novel approaches that prioritize resource efficiency without sacrificing economic success in isolating GDP growth from resource depletion is increasing. The empirical investigation delves into the complex interplay among environmental sustainability, energy innovation, and fintech to improve natural resource utilization in an emerging economy from 1998 to 2022. Using the Autoregressive Distributed Lag (ARDL) technique, we analyze how these factors interact dynamically. Our findings offer valuable insights into emerging economies natural resource utilization. In addition, empirical research elucidates a significant impact of financial technology, natural resource consumption, and environmental sustainability on economic growth, suggesting the significance of sustainable practices in effective natural resource management. This study provides valuable insight into environmental factors and government policies that influence natural resource utilization in emerging countries and the need to reevaluate economic theories and methods of resource management. It underscores the urgency of adopting sustainable practices to insignificant effects of renewable energy, while also leveraging fintech as a powerful driver for the exploitation of natural resources. The insights provided are valuable for policymakers aiming to promote a sustainable environment.